An inventory model for a deteriorating item with price-dependent demand and special sale. (15th February 2007) - Roy, T.; Chaudhuri, K.S.
Strategy of pricing is a major one for a manager of any economic sector to obtain its maximum profit. Therefore, in this article, we introduce here an order-level inventory model for a deteriorating item, taking the demand to be dependent on the sale price of the item to determine its optimal selling price and net profit. Also the concept of the special sale campaign for a festive season or for the purpose of clearance sale by way of price reduction is incorporated into the model. It is seen that the economic sector runs on a net loss without price reduction and special sale campaign. This is proved in theory and should be followed in practice. We compare two models of without special sale (Model I) and with special sale (Model II). The model is solved analytically and a numerical simulation of the results is carried out for a given data set. Sensitivity of the model for different values of G to changes in the parameter values is also examined.